Amino-functionalized conjugated polymer electron transport layers enhance the UV-photostability of planar heterojunction perovskite solar cells. Issue 6 (5th May 2017) - Li, Dan; Sun, Chen; Li, Hao; Shi, Hui; Shai, Xuxia; Sun, Qiang; Han, Junbo; Shen, Yan; Yip, Hin-Lap; Huang, Fei; Wang, Mingkui
Abstract : Long-term photostability and high performance were achieved by perovskite solar cells with an amino-functionalized conjugated polymer as a new electron transport layer. Abstract : In this study, for the first time, we report a solution-processed amino-functionalized copolymer semiconductor (PFN-2TNDI) with a conjugated backbone composed of fluorine, naphthalene diimide, and thiophene spacers as the electron transporting layer (ETL) in n–i–p planar structured perovskite solar cells. Using this copolymer semiconductor in conjunction with a planar n–i–p heterojunction, we achieved an unprecedented efficiency of ∼16% under standard illumination test conditions. More importantly, the perovskite devices using this polymer ETL have shown good stability under constant ultra violet (UV) light soaking during 3000 h of accelerated tests. Various advanced spectroscopic characterizations, including ultra-fast spectroscopy, ultra-violet photoelectron spectroscopy and electronic impedance spectroscopy, elucidate that the interaction between the functional polymer ETL and the perovskite layer plays a critical role in trap passivation and thus, the device UV-photostability. We expect that these results will boost the development of low temperature solution-processed organic ETL materials, which is essential for the commercialization of high-performance and stable, flexible perovskite solar cells.